Unusual gate coupling effect in extremely thin and short FDSOI MOSFETs - Chang, S. -J.; Bawedin, M.; Andrieu, F.; Navarro, C.; Kim, Y. T.; Bae, Y.; Cristoloveanu, S. (ELSEVIER, 2015)
We investigated the characteristics of state-of-the-art FDSOI MOSFETs in a wide range of temperature by focusing on the effects of the back-gate bias, Si film thickness and channel length. High device performance and remarkably reduced short-channel effect with decreasing Si film thickness are achieved in ultra-thin film SOI devices. Systematic measurements reveal an unusual coupling effect resulting from the competition between front-gate, back-gate and temperature-dependent short-channel effect. Counter-intuitively, the impact of the back-gate bias can be smaller in 5 nm than in 10 nm thick MOSFETs, in particular in very short devices operated at 300 K. (C) 2015 Elsevier B.V. All rights reserved.
Keywords: THRESHOLD VOLTAGE; DEVICES